Upaya Meningkatkan Hasil Belajar Matematika Siswa Melalui Integrasi STAD dan Penemuan Terbimbing - Yuni Rhamayani; Nurdalilah; Lubis, Nandini Faradilla Rosa (Journal Education Innovation (JEI), 2025)
This study aims to enhance students' mathematics learning outcomes through the implementation of the cooperative learning model STAD combined with the guided discovery method. The research was conducted in Class VII-2 of SMP Negeri 2 Batangtoru during the 2023/2024 academic year, focusing on fraction material. This learning model was chosen for its ability to foster collaboration among students while actively guiding them to discover learning concepts. The study employed a Classroom Action Research (CAR) approach, consisting of two cycles. Each cycle involved stages of planning, implementation, observation, and reflection. The results revealed significant improvements in students' learning outcomes between Cycle I and Cycle II. The average class score increased from 71.1 to 81, while the classical mastery level rose from 71.4% to 89.3%. Students' responses to the learning process also improved significantly, with the average questionnaire score rising from 80.4 in Cycle I to 91.6 in Cycle II. These findings confirm the effectiveness of the cooperative learning model STAD combined with guided discovery in creating a conducive learning environment and enhancing students' understanding of abstract materials. This research provides valuable insights for implementing innovative teaching methods in schools and contributes to the development of more effective and adaptive strategies for teaching mathematics.